2021
DOI: 10.1186/s12968-021-00732-5
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular magnetic resonance-determined left ventricular myocardium impairment is associated with C-reactive protein and ST2 in patients with paroxysmal atrial fibrillation

Abstract: Background Myocardial strain assessed with cardiovascular magnetic resonance (CMR) feature tracking can detect early left ventricular (LV) myocardial deformation quantitatively in patients with a variety of cardiovascular diseases, but this method has not yet been applied to quantify myocardial strain in patients with atrial fibrillation (AF) and no coexistent cardiovascular disease, i.e., the early stage of AF. This study sought to compare LV myocardial strain and T1 mapping indices in AF pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…39 Levels of ST2 are known to increase significantly in both heart failure and AF. 40,41 Here, marked enlargement of the atria of rabbits in the RAP group was seen on echocardiography, a clear indication of structural remodeling, and the LVEF was also reduced, although it did not reach the degree of HFrEF and worsening of HF. CVF levels also increased significantly in the RAP group, shown by, and western blotting and biochemical assays demonstrated raised levels of collagens I and III and ST2 in the RAP group, an indication that atrial fibrosis was a consequence of rapid pacing.…”
Section: Discussionmentioning
confidence: 92%
“…39 Levels of ST2 are known to increase significantly in both heart failure and AF. 40,41 Here, marked enlargement of the atria of rabbits in the RAP group was seen on echocardiography, a clear indication of structural remodeling, and the LVEF was also reduced, although it did not reach the degree of HFrEF and worsening of HF. CVF levels also increased significantly in the RAP group, shown by, and western blotting and biochemical assays demonstrated raised levels of collagens I and III and ST2 in the RAP group, an indication that atrial fibrosis was a consequence of rapid pacing.…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, the most prominent risk factors for AF development, such as age, sex, increased BMI, hypertension, and HF, have all been related to elevated natriuretic peptide concentrations. Previous studies showed that patients with AF had signifcantly higher CRP levels than the SR group [20], and elevated hs-CRP levels were signifcantly associated with an increased risk of AF [35][36][37]. However, circulating BNP and CRP are known biomarkers for systemic circulation and can be infuenced by many factors, such as HF and acute or chronic infammation.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the results also showed a higher serum level of sST2 in patients with persistent AF. In another study, patients with AF showed significantly higher sST2 than the control group did [ 20 ]. This study consistently found that sST2 was higher in patients with SR and increased gradually as a patient moved from SR to paroxysmal persistent AF.…”
Section: Discussionmentioning
confidence: 99%
“…Okar and colleagues reported that soluble ST2, as measured prior to an ablation procedure, is an independent parameter for predicting AF recurrence [ 11 ]. Other studies have suggested that sST2 was associated with LA volume enlargement, the LA low-voltage zone, and LV myocardium abnormalities in patients with paroxysmal AF [ 12 , 13 ]. Similar to the above findings, our results indicate that the median sST2 concentration of the pAF group was 12.76 ± 4.73 ng/ml, higher than that of the SR group.…”
Section: Discussionmentioning
confidence: 99%